Factores de riesgo en la neumonía asociada a ventilación en los pacientes de la unidad de cuidados intensivos de la Clínica Peruano Americana, Trujillo - Leiva León, Carmen Rosa (2017)
The present research study is descriptive retrospective. It was performed in the patients of the Intensive Care Unit of the Peruvian American Clinic (UCI), in order to determine the risk factors in pneumonia associated with mechanical ventilation: age, history of diseases, use of nasogastric tube, Nebulisations, aspiration of secretions and postural changes. The sample universe consisted of a total of 40 clinical records, which met the inclusion criteria. The information was obtained through the following instrument developed by the author, using the Barreda test, which was valid and reliable, applied in the medical records by filling out the questionnaire, considering the criteria of veracity, reliability and credibility. The results were statistically analyzed and presented in tables and graphs of simple and double entry in numerical and percentage form, being found that there is a statistically significant relationship (p = 0.015 <0.05) between age and pneumonia; There is a statistically significant relationship (p = 0.014 <0.05) between aspiration of secretions and the presence of pneumonia; And there is a highly significant statistical relationship (p = 0.005 <0.05) between nebulizations and the presence of pneumonia; For the statistical analysis, the Criterion Independence Test (Chi Square) was applied, and there was a relationship between some risk factors: age, nebulization and aspiration of secretions in pneumonia associated with mechanical ventilation in patients in the Care Unit Intensive. Correlation was determined using the Spearman correlation coefficient, reaching levels of statistical significance.